Bilateral agreement for academic years 2008/2013 Lifelong Learning Programme higher education Erasmus between Universidade Lusíada de Lisboa and HafenCity Universität Hamburg - Universidades Lusíada de Lisboa (2016)
- Cooperate in the activities within the Erasmus Programme. - Subject area: Architecture, Urbanism.